Taking the emotional pulse of software engineering — A systematic literature review of empirical studies - Sánchez-Gordón, Mary; Colomo-Palacios, Ricardo (Information and software technology, 2019)
Over the past 50 years of Software Engineering, numerous studies have acknowledged the importance of human factors. However, software developers’ emotions are still an area under investigation and debate that is gaining relevance in the software industry. In this study, a systematic literature review (SLR) was carried out to identify, evaluate, and synthesize research published concerning software developers’ emotions as well as the measures used to assess its existence. By searching five major bibliographic databases, authors identified 7172 articles related to emotions in Software Engineering. We selected 66 of these papers as primary studies. Then, they were analyzed in order to find empirical evidence of the intersection of emotions and software engineering. Studies report a total of 40 discrete emotions but the most frequent were: anger, fear, disgust, sadness, joy, love, and happiness. There are also 2 different dimensional approaches and 10 datasets related to this topic which are publicly available on the Web. The findings also showed that self-reported mood instruments (e.g., SAM, PANAS), physiological measures (e.g., heart rate, perspiration) or behavioral measures (e.g., keyboard use) are the least reported tools, although, there is a recognized intrinsic problem with the accuracy of current state of the art sentiment analysis tools. Moreover, most of the studies used software practitioners and/or datasets from industrial context as subjects. The study of emotions has received a growing attention from the research community in the recent years, but the management of emotions has always been challenging in practice. Although it can be said that this field is not mature enough yet, our results provide a holistic view that will benefit researchers by providing the latest trends in this area and identifying the corresponding research gaps.